On the horizon: flexible immune recognition outside lymphocytes - Kaminski, Wolfgang E.; Beham, Alexander; Kzhyshkowska, Julia; Gratchev, Alexei; Püllmann, Kerstin (Immunobiology, 2013)
Since decades there is consensus among immunologists that in jawless and jawed vertebrates flexible immune recognition is strictly confined to the lymphoid lineage. In jawed vertebrates the adaptive immune system is represented by two lineages of lymphocytes, B cells and T cells that express recombinatorial antigen receptors of enormous diversity known as immunoglobulins and the T cell receptor (TCR). The recent identification of recombined immune receptors that are structurally based on the TCR in subpopulations of neutrophils and eosinophils (referred to here as TCR-like immunoreceptors, “TCRL”) provides unexpected evidence for the existence of flexible host defense mechanisms beyond the realm of lymphocytes. Consistent with this, subpopulations of monocytes and macrophages from humans and mice now have also been shown to constitutively express recombined TCR-like immunoreceptors. Available in vitro evidence suggests that the TCRL in macrophages may exert functions as facilitators of phagocytosis and self-recruitment. More importantly, our recent findings that the macrophage-TCRL is implicated in granuloma formation in tuberculosis and the neutrophil-TCRL is associated with autoimmune hemolytic anemia establish for the first time a link between myeloid recombinatorial immune receptors and clinical disease. The discovery of recombined TCR-like immune receptors in granulocytes and macrophages extends the principle of combinatorial immune recognition to phagocytic cells. Conceptually, this unifies the two hitherto disparate cardinal features of innate and adaptive immunity, phagocytic capacity and recombinatorial immune recognition on a common cellular platform. Moreover, it strongly suggests that flexible host defense in vertebrates may operate on a broader cellular basis than currently thought.
Available online 31 May 2012
Gesehen am 12.04.2018